2018
DOI: 10.1186/s40560-018-0296-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the first interpretation of early brain CT images for predicting the prognosis of post-cardiac arrest syndrome patients at the emergency department

Abstract: BackgroundEarly brain CT is one of the most useful tools for estimating the prognosis in patients with post-cardiac arrest syndrome (PCAS) at the emergency department (ED). The aim of this study was to evaluate the prognosis-prediction accuracy of the emergency physicians’ interpretation of the findings on early brain CT in PCAS patients treated by targeted temperature management (TTM).MethodsThis was a double-center, retrospective, observational study. Eligible subjects were cardiac arrest patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Clinical data were collected retrospectively from electronic medical charts. The gray to white matter signal intensity ratio (GWR) was analyzed using brain computed tomography (CT) images of 17 patients with CA in a blinded manner using a previously described method 17,18 . The CT scan was performed within 8 hours after ROSC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data were collected retrospectively from electronic medical charts. The gray to white matter signal intensity ratio (GWR) was analyzed using brain computed tomography (CT) images of 17 patients with CA in a blinded manner using a previously described method 17,18 . The CT scan was performed within 8 hours after ROSC.…”
Section: Methodsmentioning
confidence: 99%
“…The CT scan was performed within 8 hours after ROSC. Based on our previous study, the cutoff point of 1.15 of GWR was used for dichromating 18,19 . The Cerebral Performance Categories (CPC) at hospital discharge were used to determine neurological outcome of the patients 20 .…”
Section: Methodsmentioning
confidence: 99%
“…123 Of note, the interpretation of early post-CA CT scans by emergency physicians and radiologists showed acceptable inter-rater reliability (Kappa statistics: 0.66). 124 In contrast, another study showed that interobserver variability when identifying ischemic brain injury was moderate to high (kappa statistics: 0.0–0.48) on head CT scans obtained from adults within two hours of resuscitation from out-of-hospital cardiac arrest. 125 In addition, using specialized scoring systems, extensive anoxic brain injury revealed by early CT (performed before the initiation of TTM) was associated with unfavorable outcome.…”
Section: Neuroimagingmentioning
confidence: 98%
“…Um dos trabalhos investigou o potencial papel prognóstico de uma tomografia precoce, ainda na sala de emergência, buscando identificar sinais de encefalopatia isquêmica em pacientes que posteriormente foram submetidos a CDT 19 . A presença de sinais como a perda de diferenciação entre substância branca e cinzenta ou edema cerebral foi capaz de predizer desfechos neurológicos ruins com acurácia de 1,00, isto é, probabilidade extremamente baixa de boa recuperação neurológica 19 .…”
Section: Imagemunclassified